Radio Malaysia in 1978: broadcasting nationalist and patriotic ideas in primary schools through songs - Chai, Ming Yan; Shazlin Amir Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Patriotic songs serve as symbols and catalysts of national identity. These songs, ranging from the national anthem "Negaraku" to a diverse repertoire of unofficial anthems, have played a crucial role in shaping the nation's cultural landscape and fostering a sense of unity among its diverse population. The popularity of these patriotic songs can be traced back to the nation's independence in 1957, when citizens had to learn the newly composed national anthem. The newly formed nation would require symbols that function as a catalyst for the realisation of Malaysia. The introduction of radio music education in Malaysian public schools in 1946 marked a significant milestone, as it allowed for the systemic dissemination of patriotic songs through the Radio Pendidikan (Radio Education) program. This program broadcasted songs to primary school students, exposing the younger generation to expressions of nationalism and patriotism through song. Through a thematic content analysis of the songs featured in the Radio Pendidikan 1978 program, the objective of this article aims to explore how the underlying themes of nationalism and patriotism were reflected in these musical compositions. The findings contribute to the understanding of the intersection between music, education, and nation-building; implicating the powerful influence of patriotic songs in uniting a diverse population and fostering a strong sense of national pride.